2016
DOI: 10.1186/s13578-016-0127-1
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of deubiquitinating enzymes in genomic integrity, diseases, and therapeutics

Abstract: The addition of mono-ubiquitin or poly-ubiquitin chain to signaling proteins in response to DNA damage signal is thought to be a critical event that facilitates the recognition of DNA damage lesion site, the activation of checkpoint function, termination and checkpoint response and the recruitment of DNA repair proteins. Despite the ubiquitin modifiers, removal of ubiquitin from the functional proteins by the deubiquitinating enzymes (DUBs) plays an important role in orchestrating DNA damage response as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 156 publications
(157 reference statements)
1
59
0
1
Order By: Relevance
“…Its efficacy was documented for a mouse xenograft model of myeloma and B-cell leukemia 64 . In Table 3, we list some major USP inhibitors [68][69][70][71][72][73] . However, despite the advances in DUB-targeting drug discovery, the identified compounds are still in the early stage awaiting clinical approvals.…”
Section: Pharmacological Studies For Dubsmentioning
confidence: 99%
“…Its efficacy was documented for a mouse xenograft model of myeloma and B-cell leukemia 64 . In Table 3, we list some major USP inhibitors [68][69][70][71][72][73] . However, despite the advances in DUB-targeting drug discovery, the identified compounds are still in the early stage awaiting clinical approvals.…”
Section: Pharmacological Studies For Dubsmentioning
confidence: 99%
“…The protein turnover and stability in eukaryotic cells is maintained by the ubiquitination/deubiquitination cascade (49). Our recent study found that aberrantly high levels of USP14 in the liver of obese mice and humans promote hepatosteatosis and hypertriglyceridemia by stabilizing fatty acid synthase (FASN) (32), which might increase the risk of glucose intolerance and T2DM (50).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that ubiquitination is a reversible process that is counteracted by deubiquitinating enzymes (DUBs). DUBs recognize specific sequences of ubiquitin, its substrates or the proteasome, and primarily remove ubiquitin from the target proteins to recycle the ubiquitin, to inhibit and proofread ubiquitination, or to alter the activity state of proteins (104). Based on their Ub-protease domains, DUBs are divided into five subclasses consisting of ubiquitin C-terminal hydrolases, ubiquitin-specific proteases (USPs), ovarian tumor-related proteases, JAB1/PAB1/MPN-domain-containing metallo-enzymes, and Machado-Joseph disease protein domain proteases (105).…”
Section: Overview Of Ubiquitination and Deubiquitinationmentioning
confidence: 99%